2015
DOI: 10.20396/sss.v12i1.8635761
|View full text |Cite
|
Sign up to set email alerts
|

ROSA, L. C. S. Transtorno mental e o cuidado na família. 3.ed. São Paulo: Cortez, 2011

Abstract: Resenha de livro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
45

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 0 publications
0
2
0
45
Order By: Relevance
“…Accordingly, the triad -users, family members, and services, should be considered in an interrelated way when proposing studies regarding the evaluation of the quality of the mental health services [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the triad -users, family members, and services, should be considered in an interrelated way when proposing studies regarding the evaluation of the quality of the mental health services [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Se trata de un estudio de campo, en el que los encuestados eran 8 trabajadores sociales y se analizaron sus líneas de base en el método dialéctico de Marx (1989), en una búsqueda para la reproducción ideal del movimiento real. Así, tratamos de reconstruir el proceso objeto históricamente dada, además de su apariencia fenoménica, como resultado de una elaboración teórica, basada en la literatura sobre el tema, con énfasis en Iamamoto (2001;, Rosa (2008) Además de la utilización de los datos y documentos de la Secretaría de Salud (BRASIL, 2004;2012). Se encontró que la mayoría de los usuarios de estos servicios son personas que, además de sufrir de trastorno mental también sufren de la pobreza y sus consecuencias, lo que requerirá la atención del trabajador social que va más allá de la atención de salud mental, de pasar la diversas expresiones de las cuestiones sociales.…”
Section: Las Expresiones De Cuestión Social En Salud Mental: Un Análiunclassified
“…It is a field survey, in which respondents were 8 social workers and analyzed his lines based on the dialectical method of Marx (1989), in a quest for ideal reproduction of the real movement. So, we tried to reconstruct the process object historically given, in addition to its phenomenal appearance, resulting from a theoretical elaboration , based on the literature on the subject , with an emphasis on Iamamoto (2001 ; , Rosa (2008) apart from the use of data and documents of the Ministry of Health (BRASIL, 2004;2012) . It was found that most users of these services are people who, besides suffering with mental disorder also suffer from poverty and its consequences, which will require the social worker attention that goes beyond mental health care , spending the various expressions of social issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa desconstrução para uma nova construção causou certo incômodo. Para Rosa (2003) em "um 'mundo' tido como organizado, imutável, o 'novo' pode representar uma ameaça ao instituído, à ordem, assim, pode ser visto com restrição" (p. 21). Porém, Freire (2006) refere que é fundamental aceitar o novo e correr riscos, mudar.…”
Section: Implantação Da Política De Educação Permanente Em Saúdeunclassified